First report of population dynamics of oleander Aphid, Aphis nerii (Hemiptera: Aphididae) on three different species of oleander shrubs in Iraq - Rabeea, A. A. (International Journal of Agricultural Technology, 2021)
The results revealed that Aphis nerii were presented on oleander plants from the end of December until the beginning of the June. The insects appeared on the bottom portion of the plants which has red, white, and pink colors, during December, and they reached their peak in February. The activity period of the insect was affected by environmental conditions, especially temperature and relative humidity (RH). At the beginning of March, insects began to move to the middle portion of the plants to for feeding the fresh leaf either on the lower or upper surface. They in the middle portion of the plant reached to peak in April. Insects moved to the top of the plant with increasing temperature at the end of March., The number of insects' increased quickly and reached its peak in May. Under laboratory conditions, Alpha cypermethrin at dosage state the was more effective, than Thiamethoxam and Abamectin. Alpha cypermethrin was mostly effective at 0.001ppm concentration. Alpha cypermethrin was harm and caused maximum mortality, which reached (100%) at the concentration of 0.001ppm followed by Thiamethoxam and Abamectin. Also, the result showed that the least effective treatment was Abamectin with only 33.33% mortality at 0.025ppm concentration. In laboratory, the condition was found to be mortality percentage dose and the type of the insecticide dependent. Experiments showed in laboratory that Alpha cypermethrin was the most toxic, followed by Thiamethoxam and Abamectin with LC50 values 0.02, 0.03, and 0.04 mg/L, respectively. Finally, this study could contribute as a guideline for pest risk assessment to protect oleander shrubs against the heavy infestation of Aphis nerii